Gaffers, Gofers, and Grips: Role-Based Coordination in Temporary Organizations - Bechky, Beth A. (Organization Science, 2006)
Temporary organizations are known to provide flexibility for industries that rely on them, but we know little about their implications for how work is accomplished and coordinated. In this paper, I propose that common portrayals of temporary organizations as ephemeral and unstable are inaccurate: Temporary organizations are in fact organized around structured role systems whose nuances are negotiated in situ. This paper analyzes one type of temporary organization, film projects, exploring the way in which roles both organize immediate work and maintain continuity across different projects. On each film set, role expectations are communicated through practices of enthusiastic thanking, polite admonishing, and role-oriented joking, which enable crew members to learn and negotiate role structures. Two important structural characteristics of film projects provide the organizational context within which coordination takes place: interorganizational career progression and projects as temporary total institutions. By showing how these structural elements and role enactments support one another, this work generates a more complete understanding of the conditions that affect coordination, including role duration, expectations of future interaction, and visibility of work.